EXPERIENTIAL LEARNING METHODS IMPROVES RATIONAL PRESCRIBING SKILL IN MEDICAL STUDENTS - Mega Pandu Arfiyanti; Gandes Retno Rahayu; Eti Nurwening Sholikhah (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2021)
Background: Rational prescribing is an important skill for medical doctors. Many graduates still feel insufficiently prepared to make rational prescribing and fail to demonstrate the related clinical reasoning after graduation. For these reasons, it is important to improve the medical student teaching of rational prescribing. The aim of this study is proving the effectiveness of experiential learning methods to improve rational prescribing skills of medical students.Methods: This study used a one-group pretest-posttest design. Rational prescribing courses use experiential learning methods for 6 year medical students. Every student provided evaluation of rational prescribing and clinical reasoning through pretest and posttest, and we analyzed the results by paired t test.Results: The change in the rational prescribing skill of the students is significant between pretest and posttest. However, in the hypertension case the scores are not significant between pretest and posttest. Also, the scores of clinical reasoning based on drug interaction and evidence based methods are not significant in the hypertension and otitis media cases.Conclusions: Experiential learning methods can enhance rational prescribing skill in medical students but the students were still not able to choose appropriate medications based on drug interaction and evidence based approach.